DEVELOPMENT OF MOROTAI ISLAND TOURISM DESTINATIONS, A TROPICAL PARADISE IN NORTH MALUKU PROVINCE - Watriningsih; Meiliyah Ariani; Zulhawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Morotai Island Regency as one of the tourist destinations that has the potential for natural and cultural tourism that has the potential to be developed into an attraction for tourist visits, both domestic and foreign tourists. The charm of Morotai Island is able to divert the eyes of tourists so that more tourists come to Morotai Island and enjoy the beautiful charm of amazing tourist objects, with the charm of natural tourism and strong historical tourism able to make Morotai Island one of the 4 favorite tourist attractions in North Maluku by foreign tourists and domestic tourists. The purpose of this study was conducted to describe the strategy of the concept of developing the promotion of Marine Tourism and Historical Tourism as a strengthening of Identity as a tropical paradise region to attract tourist visits to Morotai Regency, North Maluku Province. The concept of marine ecotourism as the right model for the development base of tourist objects and attractions owned by Morotai Island Regency. The development of historical tourism in Morotai Island Regency can be in line with strengthening the identity of Morotai Island Regency as an area that became part of the history of World War II, by providing direction for the design of elements forming the image of the region, namely paths, nodes, landmarks, districts, and edges, based on the historical value of Morotai Island Regency. From the results of this study, recommendations can be given to the Regional Government of Morotai Island Regency to be able to develop and promote marine and historical tourism destinations in Morotai Island Regency as the main tourist attraction, and the natural beauty of Morotai Island Regency is an additional attraction that supports tourism potential in Morotai Island Regency as a whole.